HUBUNGAN SUAMI ISTRI DALAM AL-QUR’AN PERSPEKTIF MUHAMMAD ‘ALI AL-SABUNI: Analisis Mubadalalah terhadap Tafsir Rawai’ al-Bayan Tafsir Ayat al-Ahkam min al-Qur’an - Rida Amalia Ningrum; Nurkholidah Nurkholidah (UIN Siber Syekh Nurjati Cirebon, 2023)
This article aims to show Muhammad 'Ali al-Sabuni's interpretation of the verses on husband and wife relations in one of his works entitled